Surgery versus stereotactic radiotherapy for people with single or solitary brain metastasis - Fuentes, Rafel (Cochrane Database Syst Rev, 2018)
BACKGROUND: Brain metastases occur when cancer cells spread from their original site to the brain and are a frequent cause of morbidity and death in people with cancer. They occur in 20% to 40% of people during the course of their disease. Brain metastases are also the most frequent type of brain malignancy. Single and solitary brain metastasis is infrequent and choosing the most appropriate treatment is a clinical challenge. Surgery and stereotactic radiotherapy are two options. For surgery, tumour resection is performed using microsurgical techniques, while in stereotactic radiotherapy, external ionising radiation beams are precisely focused on the brain metastasis. Stereotactic radiotherapy may be given as a single dose, also known as single dose radiosurgery, or in a number of fractions, also known as fractionated stereotactic radiotherapy. There is uncertainty regarding which treatment (surgery or stereotactic radiotherapy) is more effective for people with single or solitary brain metastasis. OBJECTIVES: To assess the effectiveness and safety of surgery versus stereotactic radiotherapy for people with single or solitary brain metastasis. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL, Issue 3, March 2018), MEDLINE and Embase up to 25 March 2018 for relevant studies. We also searched trials databases, grey literature and handsearched relevant literature. SELECTION CRITERIA: We included randomised controlled trials (RCTs) comparing surgery versus stereotactic radiotherapy, either a single fraction (stereotactic radiosurgery) or multiple fractions (fractionated stereotactic radiotherapy) for treatment of single or solitary brain metastasis. DATA COLLECTION AND ANALYSIS: Two review authors screened all references, evaluated the quality of the included studies using the Cochrane tool for assessing risk of bias, and performed data extraction. The primary outcomes were overall survival and adverse events. Secondary outcomes included progression‐free survival and quality of life . We analysed overall survival and progression‐free survival as hazard ratios (HRs) with 95% confidence intervals (CIs), and analysed adverse events as risk ratios (RRs). For quality of life we used mean difference (MD). MAIN RESULTS: Two RCTs including 85 participants met our inclusion criteria. One study included people with single untreated brain metastasis (n = 64), and the other included people with solitary brain metastasis (22 consented to randomisation and 21 were analysed). We identified a third trial reported as completed and pending results this may be included in future updates of this review. The two included studies were prematurely closed due to poor participant accrual. One study compared surgery plus whole brain radiotherapy (WBRT) versus stereotactic radiosurgery alone, and the second study compared surgery plus WBRT versus stereotactic radiosurgery plus WBRT. Meta‐analysis was not possible due to clinical heterogeneity between trial interventions. The overall certainty of evidence was low or very low for all outcomes due to high risk of bias and imprecision. We found no difference in overall survival in either of the two comparisons. For the comparison of surgery plus WBRT versus stereotactic radiosurgery alone: HR 0.92, 95% CI 0.48 to 1.77; 64 participants, very low‐certainty evidence. We downgraded the certainty of the evidence to very low due to risk of bias and imprecision. For the comparison of surgery plus WBRT versus stereotactic radiosurgery plus WBRT: HR 0.53, 95% CI 0.20 to 1.42; 21 participants, low‐certainty evidence. We downgraded the certainty of the evidence to low due to imprecision. Adverse events were reported in both trial groups in the two studies, showing no differences for surgery plus WBRT versus stereotactic radiosurgery alone (RR 0.31, 95% CI 0.07 to 1.44; 64 participants) and for surgery plus WBRT versus stereotactic radiosurgery plus WBRT (RR 0.37, 95% CI 0.05 to 2.98; 21 participants). Most of the adverse events were related to radiation toxicities. We considered the certainty of the evidence from the two comparisons to be very low due to risk of bias and imprecision. There was no difference in progression‐free survival in the study comparing surgery plus WBRT versus stereotactic radiosurgery plus WBRT (HR 0.55, 95% CI 0.22 to 1.38; 21 participants, low‐certainty evidence). We downgraded the evidence to low certainty due to imprecision. This outcome was not clearly reported for the other comparison. In general, there were no differences in quality of life between the two studies. The study comparing surgery plus WBRT versus stereotactic radiosurgery plus WBRT found no differences after two months using the QLQ‐C30 global scale (MD ‐10.80, 95% CI ‐44.67 to 23.07; 14 participants, very low‐certainty evidence). We downgraded the certainty of evidence to very low due to risk of bias and imprecision. AUTHORS' CONCLUSIONS: Currently, there is no definitive evidence regarding the effectiveness and safety of surgery versus stereotactic radiotherapy on overall survival, adverse events, progression‐free survival and quality of life in people with single or solitary brain metastasis, and benefits must be decided on a case‐by‐case basis until well powered and designed trials are available. Given the difficulties in participant accrual, an international multicentred approach should be considered for future studies.